![image](https://tex.z-dn.net/?f=y+%3D+log_%7B4%7D%28+%7Bx%7D%5E%7B2%7D+-+3x+%29+%5C%5C+odz+%5C%3A+%5C%5C+%7Bx%7D%5E%7B2%7D+-+3x+%3E+0+%5C%5C+x%28x+-+3%29+%3E+0+%5C%5C+x%28x+-+3%29+%3D+0+%5C%5C+x+%3D+0+%5C%3A+%5C%3A+%5C%3A+and+%5C%3A+%5C%3A+%5C%3A+x+%3D+3+%5C%5C+%2B+%2B+%2B+%2B+%280%29+-+-+-+-+%283%29+%2B+%2B+%2B+%2B+%5C%5C+x%5Cin%28+-+%5Cinfty%3B0%29%5Ccup%283%3B+%2B+%5Cinfty%29)
0 \\ x(x - 3) > 0 \\ x(x - 3) = 0 \\ x = 0 \: \: \: and \: \: \: x = 3 \\ + + + + (0) - - - - (3) + + + + \\ x\in( - \infty;0)\cup(3; + \infty)" alt="y = log_{4}( {x}^{2} - 3x ) \\ odz \: \\ {x}^{2} - 3x > 0 \\ x(x - 3) > 0 \\ x(x - 3) = 0 \\ x = 0 \: \: \: and \: \: \: x = 3 \\ + + + + (0) - - - - (3) + + + + \\ x\in( - \infty;0)\cup(3; + \infty)" align="absmiddle" class="latex-formula">